2018
DOI: 10.3390/met8120992
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Force Model for Thermal-Assisted Machining of Tool Steel Based on the Taguchi Method

Abstract: This paper investigates cutting force in thermal-assisted machining (TAM) by induction heating for SKD11 tool steel which is widely used in the mold industry. Experimental studies were first conducted at room and elevated temperatures to evaluate the effectiveness of the heating process on chip morphology and the cutting forces during the thermal-assisted machining and comparing with conventional machining method. The Taguchi method based on orthogonal array and analysis of variance ANOVA method was then used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…After collecting results, the data were analyzed using ANOVA in Minitab 18 software. With the target function of the least grinding time, the criterion LB was selected for the S/N ratio, and it is described by the following equation [6][7][8][9][10][11][12][13][14]:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After collecting results, the data were analyzed using ANOVA in Minitab 18 software. With the target function of the least grinding time, the criterion LB was selected for the S/N ratio, and it is described by the following equation [6][7][8][9][10][11][12][13][14]:…”
Section: Resultsmentioning
confidence: 99%
“…The impact of each parameter was determined by using S/N ratio, which helped to find the strength of experiments for the optimization of cutting parameters [9]. There exist three quality characteristics of the Taguchi technique known as the higher-the-better (HB), the lower-the-better (LB) and the nominal-the-best (NB) [6][7][8][9][10][11][12][13][14]. In this study, LB criterion was selected to be corresponding to the objective to achieve the least grinding time [6][7][8][9][10][11][12][13][14].…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although traditional techniques like diamond grinding or discharge machining are limited by high costs and specialized technologies, TAM has been introduced as an innovative solution to the challenges of machining SKD11. Studies have indicated that machining with TAM can reduce cutting forces by up to 40%, increase tool life, enhance surface roughness by up to 50%, and increase material removal rate when compared to machining at room temperature [11][12][13].…”
Section: Introductionmentioning
confidence: 99%